2012
DOI: 10.4028/www.scientific.net/amr.626.152
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Treated Palm Oil Fuel Ash and its Effects on Properties of High Strength Concrete

Abstract: Palm oil fuel ash obtained from palm oil mill was treated via screening, grinding and heating to improve its pozzolanic reactivity. The characteristics of the palm oil fuel ash before and after treatment were monitored to assess the changes in the properties of the palm oil fuel ash. The resulting ultrafine palm oil fuel ash was then utilized to produce high strength concrete by replacing the ordinary Portland cement at 0, 20, 40 and 60% on mass-for-mass basis. The results show that the treatment process under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
2
5
0
1
Order By: Relevance
“…1. This process was similar to that reported previously by Zeyad et al (2013) and also by Chandara et al (2010) but without the second stage grinding. The physical properties and chemical compositions of OPC and UPOFA are provided in Table 1 and Table 2, respectively.…”
Section: Experimental Worksupporting
confidence: 91%
“…1. This process was similar to that reported previously by Zeyad et al (2013) and also by Chandara et al (2010) but without the second stage grinding. The physical properties and chemical compositions of OPC and UPOFA are provided in Table 1 and Table 2, respectively.…”
Section: Experimental Worksupporting
confidence: 91%
“…al. [34], and Chandara et al [35] have also found similar results. At this stage, POFA had turned from black to brownish color [28]; this form of POFA is known as the treated mPOFA.…”
Section: Methodssupporting
confidence: 58%
“…The chemical properties of POFA depend on the burning process, the raw materials used and the burning temperature [20,21]. Treatment of POFA to improve the chemical compositions properties and physical properties by grinding and thermal treatment to increase the fluidity, fineness and effectiveness leads to enhanced strength properties [22]. It is found that utilizing POFA to treat soft clays increased the plastic limit, and overall, utilizing POFA in soft clay treatment reduces the plasticity and improves the consistency of the treated soil, which can be attributed to the agglomeration and flocculation that occurred in the particles of the stabilized soil, as found by [23,24].…”
Section: Introductionmentioning
confidence: 99%